Introduction: importance of South American underground starchy crops - Cereda, Marney Pascoli [UNESP]; Vilpoux, Olivier François (Elsevier, 2022)
In Latin America, underground starchy crops are considered as very important in the fixation of humans through agriculture. As they are stored in the soil, they are less susceptible to attacks by pests and diseases than cereals. In addition to being used fresh as food and animal feeds, these crops can be processed and have extended storage. In this collection namely “Underground starchy crops of South American origin: Production, Processing, Utilization, and Economic Perspectives,” we focus on the production and use of starch, an international as well as versatile product. Cassava and potatoes, native of the Amazon and the Andean highlands regions, are widely used for starch extraction, but these also have other under-exploited potentials. This chapter presents some main crops and emphasizes the lack of knowledge about these crops, except for potato and cassava(the main crops), with few scientific publications in English.
Keywords: arrowroot; cocoyam; mashua; oka; Olluco; Peruvian carrot; taniacoco